A decade of proxy internet use: The changing role of socio-demographics and family support in nonusers' indirect internet access to online services. Issue 4 (15th August 2022) - Grošelj, Darja; Reisdorf, Bianca C.; Dolničar, Vesna; Petrovčič, Andraž
Abstract: Internet nonuse persists among the most excluded groups of people, particularly among aging and low-educated populations. Proxy internet use (PIU), where nonusers ask internet users to do things online for them, helps nonusers mitigate their exclusion from the digital realm. This study examines the changing factors that shape PIU activation. Specifically, it focuses on the changing role of socio-demographics and family support in internet nonusers' access to online services by comparing factors engendering active engagement in PIU in 2009 and 2018. The results from multivariate analyses of cross-sectional survey data from two nationwide representative samples collected nine years apart in Slovenia show that both sets of factors have lost their explanatory power over time. At the same time, internet nonusers are increasingly concentrated in the most vulnerable groups of people. Specifically, the decreasing importance of (grand)children as proxy users and the newly emerging importance of spouses or partners represents a shift away from inter generational support and toward intra generational support in regards to who nonusers rely on when asking for help with online tasks and services.